A41 LOSS OF SATB2 EXPRESSION IN COLORECTAL CANCER IS ASSOCIATED WITH DURATION OF INFLAMMATORY BOWEL DISEASE. (26th February 2020) - Atin, J; Hernandez-Rocha, C; Borowski, K; Stempak, J; Smith, M; Conner, J R; Silverberg, M
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at higher risk for developing colitis-associated colorectal cancer (CAC). Clinical and endoscopic features are used to stratify the risk of CAC, but new biomarkers are necessary to improve this stratification. Recent studies have shown that loss of expression of special AT-rich sequence binding protein 2 (SATB2) is frequent in CAC compared to sporadic colorectal cancer and this SATB2 status is found in pre-cancerous dysplastic lesions as well. However, the relationship of known clinical risk factors for CAC and loss of SATB2 has not been explored. Aims: To assess the association of loss of SATB2 expression in CAC with clinical characteristics of IBD. Methods: Patients with a known diagnosis of ileocolonic or colonic Crohn's disease (CD), ulcerative colitis (UC), or IBD unclassified (IBDU) who underwent colectomy between October 2010 and December 2017 for CAC were included. SATB2 expression in neoplastic tissue was evaluated using immunohistochemistry (IHC), where less than 5% of tumor cells showing staining was considered loss of SATB2. Tumor grade, P53 and mismatch repair (MMR) status were assessed as well. Available clinical data such as sex, smoking status, IBD diagnosis (CD, UC or IBDU), age at IBD diagnosis, duration of IBD, extent of colitis and previous medications were collected. We used a generalized linear model to assess the association between these biomarkers and clinical data. Results: A total of 58 patients with mean age at CAC diagnosis of 50.3 ±13 years, 27 (46%) females were analyzed. Mean IBD duration was 17.6 ±10 years and 22 (37.9%), 34 (58.6%) and 2 (3.4%) were CD, UC and IBDU, respectively. Thirty-two (55.2%) CACs had loss of SATB2 expression. There was no association between age at CAC diagnosis or grade of the tumor and loss of SATB2. However, longer duration of IBD (21.2 ± 9 years vs 13.7 ± 9 years, p = 0.01) was significantly associated with loss of SATB2. There was no association between SATB2 status and other explored clinical or endoscopic variables. Tumors with P53 mutation were associated with a younger age at diagnosis of CAC (47.2 ±13 vs 55.0 ±12 years, p = 0.03), but no other associations of this marker or MMR with clinical or endoscopic variables of IBD were found. Conclusions: Loss of SATB2 expression is significantly associated with IBD duration, a well-known risk factor for CAC. This association with duration of IBD could denote an effect of longer chronic inflammation on SATB2 status. Given the previously reported association of loss of expression of SATB2 with pre-cancerous lesions in IBD patients, this could be a potential biomarker for risk of CAC. Funding Agencies: National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK)